The role of preoperative axillary lymph node marking with a clip in breast cancer patient - Nesma Naguib Elsayed; Lobna Abdelmoneam Habib (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Locally advanced breast cancer is treated with neoadjuvant chemotherapy, followed by surgical intervention. Lymph node dissection surgery has great morbidity and mortality, so it is replaced with neoadjuvant chemotherapy (NAC), which leads to the conversion of the positive lymph nodes into negative, followed by targeted axillary clearance. The accuracy of restaging of the lymph node status after NAC has a great effect on the prognosis and treatment plan of breast cancer patients. Proper surgical localization of the metastatic lymph nodes helps surgeon to avoid total axillary clearance. Sentinel lymph node biopsy (SLNB) can identify metastasis; yet, false negative results have been reported in multiple previous studies. The study aimed to detect the role of preoperative ultrasound-guided axillary lymph node marking with a clip to facilitate visualization after neoadjuvant chemotherapy and proper surgical localization of the affected lymph nodes to decrease the rate of total axillary clearance. We included 30 female patients with breast cancer with pathologically proven metastatic axillary lymph nodes. The results were compared with those of 30 other female patients who had not undergone clips application to the metastatic axillary lymph nodes. In our study, the cases completed their chemotherapy, wire localization of the clipped lymph nodes was done before surgery to facilitate surgical localization of the previously noted pathological lymph node. Results This study was conducted on 60 female patients with primary breast lesions with pathologically proven breast cancer divided into two equal groups regarding clips application (controls ‘didn’t apply’ and cases ‘apply’); among the cases, complications after clips were insignificant. The most frequent complication was pain, which was found in 16.67% of patients, hematoma in 6.67%, and displacement in 3.33%, but there was no evidence of infection in any of our patients after clip insertion. Regarding visualization of lymph nodes before and after chemotherapy between two study groups, all LNs were visualized before chemotherapy, while there was a decrease in the number of patients who had visualized LNs in the control group 22 (73.3%) more than cases group 28 (93.33%) with a significant decrease in the control group (P value = 0.038). Twenty patients from the cases completed their chemotherapy treatment and prepared for surgery. Wire localization enables surgeons to identify the clipped lymph nodes in all the participating cases. This allows surgeons to undergo tailored axillary clearance instead of total axillary clearance. Conclusions We concluded from our study that the utilization of axillary lymph node markers is obligatory before NAC. This is done by a simple procedure with no significant complications could be detected. This aids in proper visualization of the site of the lesion and proper follow-up after the neoadjuvant chemotherapy. Wire localization of the clipped lymph nodes facilitates surgical identification of the previously noted metastatic lymph nodes and this leads to a decrease in the rate of total axillary clearance and a decrease in the morbidity after surgery.